Membangun Fondasi Keuangan Yang Kuat: Peran Literasi Keuangan Dalam Meningkatkan Keberlangsungan UMKM - Firman Fauzi; Agung Hudaya (Lembaga Pengembangan Kinerja Dosen, 2024)
It is expected that UMKM will become a leading economic sector in order to achieve its building goals. This is due to the fact that UMKM is one of the few businesses that can thrive in challenging economic conditions. Due to this, in order for UMKM to be able to continue, UMKM has to have sound financial management practices. The first is having accurate financial knowledge and the ability to create financial reports that are needed to formulate business strategies that will eventually emerge. The financial performance of East Sudimara Culinary MSME in Ciledug, Tangerang does not reflect a sound financial performance. Training and mentorship outcomes, such as basic accounting and financial report writing, raise MSME actors' knowledge of the value of the information collected.